2007
DOI: 10.1007/s11738-007-0069-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salicylic acid potentiates cadmium-induced oxidative damage in Oryza sativa L. leaves

Abstract: In the present investigation, we studied the possible potentiating effect of salicylic acid (SA) under Cd toxicity in Oryza sativa L. leaves. Cd treatments for 24 h reduced the shoot length, dry biomass and total chlorophyll content followed by high Cd accumulation in shoots. About 16 h presoaking with SA resulted in partial protection against Cd, as observed by minor changes in length, biomass and total chlorophyll. SA priming resulted in low Cd accumulation. Enhanced thiobarbituric acid reactive substances (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 53 publications
(52 reference statements)
6
25
0
Order By: Relevance
“…These results are in accordance with the earlier reports demonstrate that, SA-induced protective response to DNA damaging agents (Bautz &Freese, 1960 andPatra et al, 2005). Earlier results also suggested that SA treatment led to a decrease in oxidative injuries induced by Cd Patra, 2007). The production of H 2 O 2 during abiotic stress serves as part of the signaling cascade, and increased levels of ROS might interact with SA.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in accordance with the earlier reports demonstrate that, SA-induced protective response to DNA damaging agents (Bautz &Freese, 1960 andPatra et al, 2005). Earlier results also suggested that SA treatment led to a decrease in oxidative injuries induced by Cd Patra, 2007). The production of H 2 O 2 during abiotic stress serves as part of the signaling cascade, and increased levels of ROS might interact with SA.…”
Section: Discussionsupporting
confidence: 93%
“…This may lead to an increase in the uptake and retention of water that aids in maintenance of higher RWC content and osmotic balance resulting in improved growth under Al stress. Similar results of reduced uptake of Al and Cd by salicylic acid were reported in rice, Cassia tora and maize [23] [24]. In plant growth experiments, the improved plant growth noticed with SA supplementation explains the role of SA to enhance auxin mediated root elongation.…”
Section: Discussionsupporting
confidence: 78%
“…As previously documented, the exogenous application of salicylic acid to rice (Choudhury and Panda 2004;Panda and Patra 2007) or mustard (Ahmad et al 2011) seeds significantly lowered Cd accumulation and reduced metal toxicity. Similar results were reported by Belkadhi et al (2012) for flax seedlings.…”
Section: Resultssupporting
confidence: 61%